Degradation of lipid regulators by the UV/chlorine process: Radical mechanisms, chlorine oxide radical (ClO)-mediated transformation pathways and toxicity changes. (15th June 2018) - Kong, Xiujuan; Wu, Zihao; Ren, Ziran; Guo, Kaiheng; Hou, Shaodong; Hua, Zhechao; Li, Xuchun; Fang, Jingyun
Abstract: Degradation of three lipid regulators, i.e., gemfibrozil, bezafibrate and clofibric acid, by a UV/chlorine treatment was systematically investigated. The chlorine oxide radical (ClO ) played an important role in the degradation of gemfibrozil and bezafibrate with second-order rate constants of 4.2 (±0.3) × 10 8  M −1  s −1 and 3.6 (±0.1) × 10 7  M −1  s −1, respectively, whereas UV photolysis and the hydroxyl radical (HO ) mainly contributed to the degradation of clofibric acid. The first-order rate constants ( k ′) for the degradation of gemfibrozil and bezafibrate increased linearly with increasing chlorine dosage, primarily due to the linear increase in the ClO concentration. The k ′ values for gemfibrozil, bezafibrate, and clofibric acid degradation decreased with increasing pH from 5.0 to 8.4; however, the contribution of the reactive chlorine species (RCS) increased. Degradation of gemfibrozil and bezafibrate was enhanced in the presence of Br −, whereas it was inhibited in the presence of natural organic matter (NOM). The presence of ammonia at a chlorine: ammonia molar ratio of 1:1 resulted in decreases in the k ′ values for gemfibrozil and bezafibrate of 69.7% and 7%, respectively, but led to an increase in that for clofibric acid of 61.8%. Degradation of gemfibrozil by ClO was initiated by hydroxylation and chlorine substitution on the benzene ring. Then, subsequent hydroxylation, bond cleavage and chlorination reactions led to the formation of more stable products. Three chlorinated intermediates were identified during ClO oxidation process. Formation of the chlorinated disinfection by-products chloral hydrate and 1, 1, 1-trichloropropanone was enhanced relative to that of other by-products. The acute toxicity of gemfibrozil to Vibrio fischeri increased significantly when subjected to direct UV photolysis, whereas it decreased when oxidized by ClO . This study is the first to report the transformation pathway of a micropollutant by ClO . Graphical abstract: Highlights: Lipid regulators were efficiently degraded by UV/chlorine. ClO. primarily contributed to the degradation of gemfibrozil and bezafibrate. ClO. transformed gemfibrozil through hydroxylation and chlorine substitution. Acute toxicity of the transformation products of gemfibrozil by ClO. was lower than UV photolysis.